2020
DOI: 10.1007/s11125-020-09483-0
|View full text |Cite
|
Sign up to set email alerts
|

Collective impacts on a global education emergency: The power of network response

Abstract: The COVID-19 pandemic is an emergency of an exceptional scale, with major impacts on education globally and with significant new challenges for education in existing humanitarian contexts. This Viewpoint reflects on the immediate challenges of continuing education in humanitarian contexts and on the experience of the Inter-agency Network for Education in Emergencies (INEE) as a network supporting collective action of Education in Emergencies (EiE) practitioners globally. It also looks forward at INEE's plans t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
3
0
2
Order By: Relevance
“…e properties of the synthesis operator are analyzed through the following nonlinear fuzzy matrix [28]:…”
Section: Evaluating the Properties Of Matrix Compositionmentioning
confidence: 99%
“…e properties of the synthesis operator are analyzed through the following nonlinear fuzzy matrix [28]:…”
Section: Evaluating the Properties Of Matrix Compositionmentioning
confidence: 99%
“…Aunque en los últimos 20 años se ha producido una amplia literatura que insiste en el llamado de atención a los centros escolares sobre la importancia, por un lado, de generar una cultura educativa en situaciones de emergencia (entre otros, Houston, 2017;Kagawa, 2005;Meyer y Wilson, 2011;Moriarty, 2020;Vega y Loaiza, 2015) y, por otro lado, de recoger empíricamente las distintas experiencias en educación de emergencia "(to) inform educators, educational policy-makers and administrators to prevent future emergencies" (Kagawa, 2005, p. 500), este llamado no se ha llevado a la práctica en ninguno de los dos sentidos.…”
Section: De Las Experiencias Ante El Covid-19 Hacia Una Cultura Educa...unclassified
“…Otro aporte del trabajo remite a la caracterización de los patrones identificados en los mecanismos de acción implementados por las UPA, ya que estos permiten reconocer los avances que se tienen en materia de una cultura educativa en situaciones de emergencia y, a la vez, visualizan las amenazas o factores de vulnerabilidad institucionales. Según Moriarty (2020), la educación en situaciones de emergencia, además de ser una noción teórica, también es una herramienta de cambio que, justamente, permite convertir esas amenazas y factores de vulnerabilidad en oportunidades de crecimiento institucional. En este contexto, el desafío para las universidades mexicanas consiste en aprovechar la experiencia acumulada frente a la pandemia por COVID-19 y dar paso a la elaboración de políticas institucionales para el fortalecimiento de una cultura educativa proactiva en situaciones de emergencia.…”
Section: Discusión Y Conclusionesunclassified
“…Although the teachers in the current study showed rapid acquisition of intervention skills, many were not formally trained in teaching young children with ASD or working with parents. Experts on emergency education have stated that schools and educational programs must be prepared for possible future crises similar to the COVID-19 pandemic ( Moriarty, 2020 ). Having more trained professionals can reduce coaching intensity and allow online training programs to expand more readily to reach more children and parents with fidelity, especially during educational emergencies.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%